2011
DOI: 10.1111/j.1537-2995.2011.03143.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved safety for young whole blood donors with new selection criteria for total estimated blood volume

Abstract: The safety initiative with new selection criteria for EBV led to decreased complications among donors 16 to 18 years old, such that the risk for 16-year-olds was no longer different from that observed for 19-year-olds in the analysis stratified by age, sex, and donation status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
78
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 22 publications
(58 reference statements)
2
78
0
Order By: Relevance
“…Male first-time donors who drank all of the water also showed an 18% difference when compared with male first-time donors who did not drink the water (4.6% vs. 5.5%; OR 0.82, 95% CI 0.62-1.09), but it did not reach a statistical difference. That male first-time donors do benefit from drinking 16 oz of water is consistent with the decrease in vasovagal reactions rates in all ARC male, high-school, first-time donors in 2008 [20], in the study by Tomasulo et al [19] that showed a 21% reduction in men with EBVs greater than 3.5 l, and in data from 8,894 high-school donors in 2004 and 2005 [51]. …”
Section: Reducing Vasovagal Reactions and Increasing Donor Retentionsupporting
confidence: 49%
See 4 more Smart Citations
“…Male first-time donors who drank all of the water also showed an 18% difference when compared with male first-time donors who did not drink the water (4.6% vs. 5.5%; OR 0.82, 95% CI 0.62-1.09), but it did not reach a statistical difference. That male first-time donors do benefit from drinking 16 oz of water is consistent with the decrease in vasovagal reactions rates in all ARC male, high-school, first-time donors in 2008 [20], in the study by Tomasulo et al [19] that showed a 21% reduction in men with EBVs greater than 3.5 l, and in data from 8,894 high-school donors in 2004 and 2005 [51]. …”
Section: Reducing Vasovagal Reactions and Increasing Donor Retentionsupporting
confidence: 49%
“…The ARC and the Blood System Institute (BSI) therefore use the variables of weight, height, and sex to determine the most accurate EBV in younger blood donors. Younger blood donors with EBVs below 3.5 l are deferred in both systems, and this decreased the vasovagal reaction rates [19,20] and delayed vasovagal reaction rate [19]. More than 99% of the young donors eliminated for an EBV less than 3.5 l are women [19,25].…”
Section: Vasovagal Reactions - New Findings On Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations